BURUNG MERAK DALAM KARYA SENI BATIK - SRI NOVI RESTARI, Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2019)
This work aims to create a peacock shape into batik artwork that uses batik techniques with the main material mori cloth or white cloth by making words using batik canting. The canting tool is useful as transferring the wax that has been heated to the mori cloth by using remazhol color in the process of giving color to the white cloth. The method of creating this final work uses five stages,namely the stages of preparation, elaboration, synthesis, realization of concepts and completion. The work produced in the form of batik artwork that serves as a wall decoration.The number of works achieved is 10 works of batik paintingwith the title: Prestige, Prestige Resistance, Seduction, Beautiful, Flick, Move Place, Different, The Other Side, Graceful, and Attract The Attention Of Women. It is hoped that appreciation material and accompanying work in creating a better batik artwork for the future.Key Words: Peacock, Batik